Novel Multiplicity and Stability Criteria for Non-Isothermal Fixed-Bed Reactors - Bremer, Jens; Sundmacher, Kai (Frontiers in Energy Research, 2021)
With the increasing need to utilize carbon dioxide, fixed-bed reactors for catalytic hydrogenation will become a decisive element for modern chemicals and energy carrier production. In this context, the resilience and flexibility to changing operating conditions becomes a major objective for design and operation of real industrial-scale reactors. Therefore, steady-state uniqueness and multiplicity are essential measures, but so far their quantification is primarily accessible for ideal reactor concepts with zero or infinite back-mixing. Based on a CSTR cascade modeling approach, this work derives novel criteria for uniqueness and multiplicity applicable to real reactors with finite back-mixing. Furthermore, the connection to other reactor features such as stability, runaway, and parametric sensitivity is demonstrated and exemplified for CO2 methanation under realistic conditions. The new criteria indicate that thermo-kinetic multiplicities induced by back-mixing remain relevant even for high Bodenstein numbers. In consequence, generally accepted back-mixing criteria (e.g., Mears’ criterion) appear insufficient for real non-isothermal reactors. The criteria derived in this work are applicable to any exothermic reaction and reactors at any scale. Ignoring uniqueness and multiplicity would disregard a broad operating range and thus a substantial potential for reactor resilience and flexibility.